Board Characteristics and Sustainability Reporting: Environmental Agencies’ Moderating Effects - Haladu, Alhassan; Salim, Basariah Bt. (International Journal of Economics and Financial Issues, 2016)
The Paris “Climate Deal” is an indication of the seriousness at international level, being attached to environmental degradation. The efficiencies of government environmental agencies in the disclosure of environmental information by sensitive firms in Nigeria, is what the study to examine. Covering the periods 2009 to 2014, secondary data was obtained from firms’ financial, sustainability and TBL statements selected at random from six sectors of the economy. Through the use of Stata13 analytical tool, regression of the variables was carried out. The result showed an encouraging disclosure index of about 55%. In particular, all the relationships measured had significant relationships and applied the latest version of GRI (G4). Environmental agencies were also tested for their role in sustainability reporting. The study recommends nonexecutive members of the board of Directors be educated on environmental matters so as to offset their negative impact on the disclosure of environmental information. Keywords: Board Characteristics, Environmental Protection Agencies, Sensitive firms JEL Classifications: H23, R11